Reduction Behaviors of Sinter Made from Magnetite Concentrates in Reducing Process Simulated COREX Shaft Furnace - Benjing Shi; Deqing Zhu; Jian Pan; Yuxiao Xue (The Minerals, Metals and Materials Society, 2017)
COREX smelting reduction process which is freed of metallurgical coke provides a sustainable developing way for ironmaking industry. However, the shortage and high cost of pellets limit its development in China. Meanwhile, iron ore sinter has a great output in China. This work studied the reduction behaviors of sinter made from magnetite concentrates during the reducing process of COREX shaft furnace and compared the RI and RDI of sinter with BF process. The results showed that the reduction degree of sinter increased obviously during the temperature zone from 600 to 850 °C, while the reduction degradation presented rapidly aggravate in the temperature zone from 425 to 550 °C in COREX shaft furnace, and the increase of metallic iron content leads to the degradation of sinter got decreased slightly during the stage of temperature above 650 °C. Sinter got higher RI than BFprocess but also got higher RDI in low reduction temperature of 550 °C, which means sinter would have heavier disintegration in COREX shaft furnace.